Subclinical changes in deceased donor kidney proteomes are associated with 12-month allograft function post transplantation: A preliminary study - Kaisar, M; van Dullemen, L; Charles, P; Akhtar, M; Thézénas, M; Huang, H; Klooster, A; Watkins, N; Kessler, B; Ploeg, R (Lippincott Williams and Wilkins Ltd., 2018)
Background: Cerebral injury during Donation after Brain Death (DBD) may induce systemic damage affecting long-term kidney function posttransplantation. Conventional evaluation of donor organ quality as a triage for transplantation is of limited utility. Methods: We compared donor kidneys yielding opposing extremes of the continuum of posttransplantation outcomes by several common kidney biopsy evaluation techniques including Kidney Donor Profile Index (KDPI) and Remuzzi scoring, and analysed tissue from a minimal sample cohort using Label-Free Quantitation (LFQ) mass spectrometry. Further assessment of the proteomic results was performed by orthogonal quantitative comparisons of selected key proteins by immunoblotting. Results: We show that common evaluation techniques of kidney biopsies were not predictive for posttransplantation outcomes. In contrast, despite the limited cohort size, the proteomic analysis was able to clearly differentiate between kidneys yielding extreme posttransplantation outcome differences. Pathway analysis of the proteomic data suggested that outcome-related variance in protein abundance associated with profibrotic, apoptosis and antioxidant proteins. Immunoblotting confirmation further supported this observation. Conclusions: We present preliminary data indicating that there is scope for existing evaluation approaches to be supplemented by the analysis of proteomic differences. Furthermore, the observed outcome-related variance in a limited cohort was supported by immunoblotting and is consistent with mechanisms previously implicated in the development of injury and cytoprotection in kidney transplantation.